Intelligent Fuzzy TIDF-II Controller for Load Frequency Control in Hybrid Energy System. Issue 6 (2nd November 2022) - Zaheeruddin,; Singh, Kavita; Amir, Mohammad
Abstract : Due to the incorporation of hybrid renewable energy sources in a power system, power quality has been adversely influenced and caused many control issues. Consequently, the power system needs substantially more capability and flexibility in controlling and optimizing to solve these issues. The power quality problems in the hybrid system are predominantly due to frequency variations. In real-time, frequency variations happen due to random fluctuations in generation/consumption or both. Thus, the present paper employs a Fuzzy tilt integral derivative (FTID) with a filter plus double integral (FTIDF-II) control strategy for frequency control in a hybrid system. The optimized coefficients of studied controller are searched out using Whale Optimization Algorithm (WOA). To show the viability and effectiveness of the WOA-based FTIDF-II controller, its outcomes are contrasted with the existing techniques. Various transient response parameters such as settling time, peak overshoots, and undershoots are investigated for analysing the dynamic performance evaluation of the hybrid system. Further also examined that WOA-based controller is sturdier against abrupt load conditions, system parameter variations, and nonlinearities. The sturdiness is an exceptionally alluring attribute in such a situation since numerous components of the hybrid energy system might be turned (on or off), which keep running at diminished/excessive power yield, at various time moments. The proposed hybrid system has been simulated in a MATLAB environment for different load conditions to evaluate system sturdiness. The impact of superconducting magnetic energy storage (SMGE) in frequency regulation is further investigated.